Impact of Pretreatment of Wheat Grain Using Infrared Radiation on Flour Falling Number (Agricultural Engineering, 2017)
The aim of the research was to determine how time of infrared radiation heating of grains influences the falling number of flour gained from wheat variety Waluta and spelled wheat variety Schwabenkorn. Moisture content was determined in the first stage of the study and it was 12% ±1%. Then grain was moisturized to the moisture of: 14, 16 and 18%. Prepared material was subjected to infrared radiation heating at the temperature of 150°C for 30, 60, 90 and 120 seconds. The heated material was sent to milling, and the falling number was determined. It has been found that the infrared radiation heating of wheat grains prior to milling significantly affects the falling number of flour, which increases with the duration of heating grain.